How to Prevent Copper Corrosion in Drinking Water Pipes. Issue 7 (3rd September 2021) - Tang, Min; Fields, Robert E.; Buse, Helen Y.; Lytle, Darren A.; Schock, Michael R.; Harmon, Stephen M.; Kireta, Andrew G.; Triantafyllidou, Simoni
Abstract : Copper corrosion is affected by a wide variety of environmental conditions in a water system. Proper evaluation approaches are key to helping utilities prevent corrosion.